Investigation into the effect of energy density on densification, surface roughness and loss of alloying elements of 7075 aluminium alloy processed by laser powder bed fusion. (March 2022) - Li, Gan; Li, Xinwei; Guo, Chuan; Zhou, Yang; Tan, Qiyang; Qu, Wenying; Li, Xinggang; Hu, Xiaogang; Zhang, Ming-Xing; Zhu, Qiang
Highlights: The variation of volume energy density significantly affects the printing quality. The over relative density varies nearly contrarily with the crack density. Severe balling phenomenon and large gaps are detrimental to surface quality. Loss in weight of alloying element is associated with the melting point. Abstract: In this study, the effects of volume energy density (VED) on densification behaviour, surface morphology and loss of alloying elements of 7075 aluminium alloy processed by laser powder bed fusion at a broad range of processing parameters were investigated. The results showed that the overall relative density of 99.4% was obtained by averting the irregular pores and keyhole pores owing to the optimisation of processing parameters. However, the hot cracks cannot be fully removed, which was mainly attributed to the substantial columnar grains and lack of liquid backfill during the last stage of solidification. Severe balling phenomenon and large gaps between tracks were recognized as the principal causes that may worsen the surface quality. There was a good linear relationship between the VED and the loss in weight contents of low-melting-point elements Zn and Mg, despite the fact that the VED had no influence on the loss of Cu and Cr. The thermodynamic calculation and experiment showed that the weight ratio of Zn to Mg, a critical element ratio in 7075 alloy, varied inversely with VED.